Pemberdayaan UMKM dalam Pemesaran Tempe melalui Whatsaap Grub di Desa Prajegan Kecamatan Sukorejo Ponorogo - Muhammad Syafi'ul Akbar; Asfahani Asfahani; Muhtarom Muhtarom (Social Science Academic, 2025)
Tempeh is a diverse product, from side dishes to snacks. Tempeh can be found throughout Indonesia and abroad. However, marketing of tempeh products is still dominated by traditional sales. To increase tempe sales, an effective digital marketing strategy via online media is needed. The purpose of this research is to identify digital marketing opportunities and challenges in Tempe as well as strategies that can be implemented by micro, small and medium businesses in Tempe to increase sales through digital media. This research uses a qualitative approach with a literature review method. Based on the results of the literature review, digital marketing opportunities in Tempe include the increasing number of internet and social media users, changes in consumer preferences for online shopping, and diversification of digital platforms. However, the challenges that exist include limited understanding of digital marketing among MSME stakeholders, minimal budget and minimal resources. quality human resources in the field of digital marketing, although there are significant opportunities in digital marketing in Tempe, such as the increase in the number of internet and social media users and changes in consumer preferences, challenges faced by micro, small and medium enterprises (MSMEs) such as limited understanding of marketing digital, budget, and quality human resources must be addressed. Therefore, to maximize the digital marketing potential of Tempe, it is necessary to increase knowledge and skills in the field of digital marketing, as well as efficient budget management and human resource development. By overcoming these challenges, tempe MSMEs can take advantage of digital opportunities to increase sales and reach a wider market.